RELIGIUS VALUES IN TRADITIONAL SELOKO OF JAMBI MALAY (A Content Analysis Study) - Ade Rahima (Universitas Batanghari Jambi, 2015)
The objective of this research was to get a deep understanding about religius values in the traditional seloko of Jambi. This research take focus of the religius values in traditional seloko of Jambi Malay. Data in this research are traditional seloko in the texts containing religius values. Primary data were obtained from a collection of traditional seloko of Jambi Malay recorded by a team of Lembaga Adat of Jambi Province, chaired by Hasip Kalimudin Syam (Pokok-pokok Adat Pucuk Jambi Sembilan Lurah, 2001). This data were analyzing using content Analyses method was combined with hermeneutic study technique to reveal the implicit meanings of the texts in traditional seloko of Jambi Malay.The results of this research show that the religius values in the traditional seloko of Jambi Malay are related to the religius values of man’s relationship with God, man with nature, man with society, and man with himself.Keywords: traditional seloko, Jambi Malay, religius values